Evaluation of fungal bioagents for management of root-knot nematodes in ginger and turmeric fields - K V Ramana, Santhosh J Eapen, B Beena (Journal of Spices and Aromatic Crops, 2008)
Ginger (Zingiber officinale Rosc.) and turmeric (Curcuma longa L.) are important herbaceousspices cultivated extensively in different states of India. Being vegetatively propagated, theyare challenged with several pests and diseases including plant parasitic nematodes. Root-knot nematode problem in these crops is currently managed with nematicides, cover cropsand organic amendments. Realizing the scope of biological control in these crops, a series ofexperiments were conducted at Indian Institute of Spices Research, Calicut, Kerala to screenand evaluate various fungal bioagents for control of root knot nematodes (Meloidogyneincognita) infesting ginger and turmeric under field conditions. Ten antagonistic fungi wereevaluated in different field experiments conducted in root-knot infested ginger and turmericfields at two locations. The most promising isolates that suppressed root knot nematodeswere Aspergillus nidulans (Is.10), Fusarium oxysporum (Is.11), Paecilomyces lilacinus (Is.36),Trichoderma viride (Is. 25), Verticillium lecanii (Is.35) and Pochonia chlamydosporia (Is.32). Fromthese, three fungi viz. F. oxysporum, T. viride and P. chlamydosporia were further tested inginger fields using two delivery systems, soil bed application and seed rhizome dippinggenerally applicable in dry shed treatment. The final results showed that P. chlamydosporiasignificantly suppressed root knot nematodes in ginger and gave the maximum yieldirrespective of the mode of application.